Effect of applied lead on the growth and accumulation of lead in Indian spinach in three textural groups of soils (Chittagong University Journal of Biological Sciences, 2013)
Indian spinach (Basella rubra L.) was grown in earthen pots containing soils of three different textures and treated with different levels of lead. The effects of Pb treatments on growth and uptake of Pb were investigated. At the highest dose of Pb ( 50 mg Pb kg-1 soil) leaf, stem and root dry weight of Indian spinach were reduced by 22-34, 11- 43 and 30-47 %, respectively from control in clay loam, sandy clay loam and sandy loam soil, respectively. Lead concentration in leaf, stem and root generally increased with increasing rate of Pb application. The highest Pb concentrations in leaf, stem and root were obtained at 50 mg Pb kg-1 soil treatment and the values were in the ranges from 49.28 to 65.40, 57.72 to 77.51 and 46.69 to 71.78 mg kg-1, respectively. Bioaccumulation coefficients of Pb in leaf, stem and root of Indian spinach were in the ranges of 0.63- 1.94, 0.82-2.21 and 0.37-1.09, respectively. DOI: http://dx.doi.org/10.3329/cujbs.v5i1.13377 The Chittagong Univ. J. B. Sci.,Vol. 5(1 &2):113-124, 2010